Cardiovascular disease‐induced thermal responses during passive heat stress: an integrated computational study. (2nd March 2016) - Zhang, Xiancheng; Noda, Shigeho; Himeno, Ryutaro; Liu, Hao
Summary: The cardiovascular system plays a crucial role in human thermoregulation; cardiovascular diseases may lead to significantly degrading the thermoregulation ability for patients during exposure to heat stress. To evaluate the thermal responses of patients with common chronic cardiovascular diseases, we here propose an integrated computational model by coupling a two‐node thermoregulation model with a closed‐loop, multi‐compartment, lumped‐parameter cardiovascular model. This bioheat transfer model is validated, capable to predict cardiovascular functions and thermal responses under varying environmental conditions. Our results demonstrate that the cardiovascular disease‐induced reduction in cardiac output and skin blood flow causes extra elevation in core temperature during hyperthermic challenges. In addition, a combination of aging, obesity, and cardiovascular diseases shows a pronounced increase in core temperature during heat exposure, which implies that such combined effect may increase the risk of heat‐related morbidity and mortality. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We present for the first time an integrated bioheat transfer model to predict thermal responses of patients with cardiovascular diseases by coupling a two‐node thermoregulation model with a closed‐loop, multi‐compartment, lumped‐parameter cardiovascular model. With this model, we have confirmed two hypotheses: (1) the attenuated thermoregulation ability caused by cardiovascular disease can be attributed to the decreased cardiac output and skin blood flow, and (2) a combination of obesity, aging, and cardiovascular diseases can compound the risk of heat‐related morbidity and mortality.